Antioxidant Activity and Consumer Sensory Perceptions of Uru Lewu (Eleusine indica) Formulations - Sera, Agnescia Clarissa; Oktaviyani, Prisilia; Prayitno, Tommi (GHMJ (Global Health Management Journal), 2023)
The Dayak indigenous people of Central Kalimantan have traditionally used native plants as food and medicine to alleviate ailments, boost stamina, and extend life. One of these is the goosegrass or uru lewu plant (Eleusine indica), which is thought to tighten female organs after birth. However, this has not been empirically confirmed. Phytochemical examinations revealed that this plant boasts three chemicals with anticancer properties and two compounds with antioxidant properties because its bioactive component concentration can be formulated into herbal drinks, such as tea. Three tea formulations were developed and evaluated on 100 consumer panelists to determine their sensory perceptions: F1 (100% uru lewu), F2 (80% uru lewu and 20% black tea), and F3 (60% uru lewu and 40% black tea). The IC50 values for Uru Lewu and black tea in the antioxidant activity test using the DPPH technique were 133.77 mg/kg and 345.01 mg/kg, respectively. This suggests that uru lewu had nearly three times the antioxidant activity of black tea. Uru lewu had moderate antioxidant activity (higher than black tea). Based on the tea's color, aroma, and taste, the F3 tea formulation with 60% uru lewu and 40% black tea was the most chosen formulation by consumers.